2020
DOI: 10.2172/1649065
|View full text |Cite
|
Sign up to set email alerts
|

Effect of NO<sub>x</sub> and Water Variations on Iodine Loading of AgZ

Abstract: Reprocessing of used nuclear fuel will result in the release of several volatile radionuclides that need to be removed from facility off-gas streams before their release to the environment. Iodine, one of these radionuclides, is expected to be primarily released in the dissolver off-gas stream as iodine (I2) or methyl iodide (CH3I). Sorbents that target I2 and CH3I removal from the DOG stream will need to adsorb iodine under elevated temperatures and in the presence of water vapor and nitrogen oxides (NOx). Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Recent studies by ORNL confirm that water plays less of a role in CH 3 I sorption than initially thought, despite a significant difference in observed loading rates, depending on whether water is present in the gas feed stream. Greaney et al (2020) found no statistical difference observed in the loading capacity of AgZ for CH 3 I from dry and humid gas streams. The findings of Greaney et al (2020) broadly align with the findings of Chebbi et al (2021).…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…Recent studies by ORNL confirm that water plays less of a role in CH 3 I sorption than initially thought, despite a significant difference in observed loading rates, depending on whether water is present in the gas feed stream. Greaney et al (2020) found no statistical difference observed in the loading capacity of AgZ for CH 3 I from dry and humid gas streams. The findings of Greaney et al (2020) broadly align with the findings of Chebbi et al (2021).…”
Section: Introductionmentioning
confidence: 63%
“…Greaney et al (2020) found no statistical difference observed in the loading capacity of AgZ for CH 3 I from dry and humid gas streams. The findings of Greaney et al (2020) broadly align with the findings of Chebbi et al (2021).…”
Section: Introductionmentioning
confidence: 63%
“…Apparent mass gain measured with the TGA is confirmed with neutron activation analysis (NAA) at the High Flux Isotope Reactor at Oak Ridge National Laboratory. Detailed methods can be found in other works ( Greaney et al, 2020 ; Greaney et al, 2021 ).…”
Section: Iodine Abatement Experimentsmentioning
confidence: 99%
“…The capture of I species and 3 H was investigated at Oak Ridge National Laboratory in earlier studies. (Greaney et al 2020, Jubin et al 2019. Silver mordenite was identified as an optimal trap for I species.…”
Section: Off-gas Capture Technologiesmentioning
confidence: 99%